SAE Technical Paper Series 2010
DOI: 10.4271/2010-01-0843
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of CAI Combustion with Alcohol Fuels

Abstract: Due to its potential for simultaneous improvement in fuel consumption and exhaust emissions, controlled autoignition (CAI) combustion has been subject to continuous research in the last several years. At the same time, there has been a lot of interest in the use of alternative fuels in order to reduce reliance on conventional fossil fuels. Therefore, this experimental study has been carried out to investigate the effect of alcohol fuels on the CAI combustion process and on the resulting engine performance.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…HCCI engines are inherently fuel-flexible and can be operated using low-or high-grade fuels, given that the fuel-air mixture can be heated up to auto-ignition temperature of the fuel in the combus tion chamber [4], In particular, HCCI engines can be operated on primary alcohols such as ethanol and methanol [5][6][7], Alcohols are attractive alternatives to gasoline/diesel, and they are identified as fuels having potential to improve urban air quality due to their cleaner combustion characteristics [8]. Alcohols, mainly ethanol and to a lesser extent methanol, are considered as alternative fuels for in ternal combustion engines [9][10][11], Ethanol is a biomass-derived renewable fuel, which can be produced by fermentation of sugars from organic biomass materials [12]; however, methanol is mainly produced from coal-or petrol-based fuels and natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…HCCI engines are inherently fuel-flexible and can be operated using low-or high-grade fuels, given that the fuel-air mixture can be heated up to auto-ignition temperature of the fuel in the combus tion chamber [4], In particular, HCCI engines can be operated on primary alcohols such as ethanol and methanol [5][6][7], Alcohols are attractive alternatives to gasoline/diesel, and they are identified as fuels having potential to improve urban air quality due to their cleaner combustion characteristics [8]. Alcohols, mainly ethanol and to a lesser extent methanol, are considered as alternative fuels for in ternal combustion engines [9][10][11], Ethanol is a biomass-derived renewable fuel, which can be produced by fermentation of sugars from organic biomass materials [12]; however, methanol is mainly produced from coal-or petrol-based fuels and natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaner combustion and hence, reduced exhaust emissions is another benefit of these oxygenated fuels. Therefore, it is interesting to combine the advantage of HCCI combustion with oxygenated fuels [10]. Oakely et al investigated HCCI combustions on single cylinder engine using methanol and ethanol at raised intake air temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…ߟ ௧ = bp mass of fuel x calorific value of fuel (12) Brake Mean Effective Pressure: The brake mean effective pressure [27] is defined to measure engine performance and indicates an engine's capacity to produce power output over the full engine speed range. The equation is expressed as below:…”
Section: Icmer 2015mentioning
confidence: 99%
“…It also another significant research purposes to combine the advantages of HCCI combustion mode using alternative renewable oxygenated fuels. Tongroon et al [12] found that methanol showed fastest and earliest auto-ignition, followed by ethanol using optical methods investigated in HCCI combustion mode .Christensen et al [13] used a lean air-fuel mixture for HCCI engine that operated unthrottled, producing an ultra-low NO x emission result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation